Adaptive Finite-Time Disturbance Observer Based Sliding Mode Control for Dual-Motor Driving System. (27th September 2018) - Zeng, Tianyi; Ren, Xuemei; Zhang, Yao
Abstract : This paper investigates a precise tracking control method based on an adaptive disturbance observer for the dual-motor driving system. The unknown matched disturbance is fully considered and estimated in this paper, and the estimation error is proven to be finite-time convergent. A sliding mode controller based on the multiple sliding surface technique is proposed in which the disturbance is compensated. The overall system containing both the observer and the controller is proven to be stable. The tracking error is within the neighbourhood of the origin before the observer completes its convergence and converges to zero thereafter. Simulation results verify the effectiveness of the disturbance observer and the sliding mode controller.